2022
DOI: 10.1002/lsm.23514
|View full text |Cite
|
Sign up to set email alerts
|

Patient selection criteria for percutaneous anterior cervical laser versus endoscopic discectomy

Abstract: Background: Percutaneous anterior laser and anterior endoscopic cervical spine surgery are associated with less approach trauma than conventional open cervical spine surgery. The literature illustrating their appropriate use corroborated with objective outcome evidence is scarce. The authors were interested in comparing the clinical outcomes following percutaneous laser disc decompression (PLDD) versus percutaneous endoscopic disc decompression (PEDD). © 2021 Wiley Periodicals LLC. Materials and Methods: Thirt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 51 publications
(103 reference statements)
0
3
0
Order By: Relevance
“…Consequently, the patient only obtained limited relief from the hiccups with selective blocking of cervical nerve root. In addition to cervical radiculopathy, specific indication of the percutaneous technique includes soft, symptomatic contained cervical disc herniations [ 11 ]. Thus, we assume that the potential therapeutic effect of the procedure may be associated with the decompression of ventral root of cervical spinal cord, as shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the patient only obtained limited relief from the hiccups with selective blocking of cervical nerve root. In addition to cervical radiculopathy, specific indication of the percutaneous technique includes soft, symptomatic contained cervical disc herniations [ 11 ]. Thus, we assume that the potential therapeutic effect of the procedure may be associated with the decompression of ventral root of cervical spinal cord, as shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Many technical reports and case series of AECD have been published, and the reported success rates have varied from 51% to 95%. [20][21][22][23][24][25]28 Most authors have concluded that endoscopic anterior cervical procedures are efficient for selected CHD, with the benefits of minimal invasiveness. However, scientific evidence of its clinical effectiveness is yet to be sufficiently elucidated.…”
Section: Journal Reviewmentioning
confidence: 99%
“…Currently, anterior endoscopic cervical discectomy (AECD) and modified procedures have been reported to be effective in appropriately selected CDH cases. [16][17][18][19][20][21][22][23][24][25] However, technical modifications of this procedure are variable and need to be integrated and standardized.…”
Section: Introductionmentioning
confidence: 99%
“…The need to implement efficient PLDD methods is driven by the urgency to provide farmers with effective instruments for controlling and minimizing the consequences of plant leaf diseases [3]. Conventional diagnosis techniques, which heavily rely on visual examination conducted by agricultural specialists, have significant obstacles, especially in areas needing more such personnel [4]. The manual identification process is characterized by considerable work and time investment, leading to delays in identifying diseases and implementing mitigation plans.…”
Section: Introduction To Plant Leaf Disease Detectionmentioning
confidence: 99%